Índices antropométricos como preditores de hipertensão arterial em idosos residentes em uma cidade de pequeno porte - Diniz, Keila de Oliveira (2015)
Hypertension is one of the main causes of mortality in the world and a risk factor for several diseases. This illness in the elderly is associated with a significant increase in cardiovascular disorders and the incidence of disabling diseases. On the other hand, body fat is related to high blood pressure in the elderly, which can be evaluated by means of anthropometric indices. This study aimed to determine the predictive power of anthropometric indices and establish cut-off points as discriminators of arterial hypertension and identify the anthropometric indicator of obesity that best discriminates the hypertension. A cross-sectional study was conducted with a sample of 310 elderly people with ages greater than or equal to 60 years, 175 (56.5 %) women. Data collection occurred between the period of 03 /02/2014 20 /02/2014 in Ibicuí city, in Bahia. The following anthropometric indices were measured: body mass index (BMI), waist circumference (WC), waist/height ratio (WHtR) and conicity index (C-Index). In addition, collected measures of systolic and diastolic blood pressure. To identify hypertension predictors was adopted the Receiver Operating Characteristic (ROC) curves analysis, with a confidence interval of 95 %.Later, it was possible to identify the cut-off points with their respective sensitivities and specificities. The samples were analyzed respecting significance level of 5 %. After the construction of the ROC curves, it was evident that some anthropometric indices presented Area under the curve (AUC) significant, being the BMI = 0.60 (0.50 -0.70); WHeR = 0.61 (0.51 -0.71); C-Index = 0.58 (0.58 -0.68), in men. The different cut-off points of anthropometric indices with better predictive powers and their respective sensitivities and specificities were identified. It is concluded that the best areas under the ROC curve were to BMI, WHeR and C Index for the men, but such measures were not satisfactory for predicting hypertension in elderly women. It is suggested that the use of two indices simultaneously can result in greater efficiency in the assessment of the risk of hypertension in the elderly.